Transforming informal communication in the urgent shift to teleworking: a case study in Japan - Watanabe, Kentaro; Umemura, Hiroyuki; Mori, Ikue; Amemiya, Saya; Yamamoto, Yuji (Frontiers in Communication, 2024)
Introduction: While informal communication is essential for employee performance and well-being, it is difficult to maintain in telework settings. This issue has recently been becoming more prominent worldwide, especially because of the coronavirus disease 2019 (COVID-19). Nevertheless, how employees managed their informal communication in the sudden shift to teleworking is still understudied. This study fills this research gap by clarifying how an organization’s employees improvised informal communication during the urgent shift to teleworking. Methods: An exploratory case study of a large construction firm in Japan was conducted, focusing on how employees improvised informal communication during teleworking in response to COVID-19. The authors conducted semi-structured interviews with 24 employees and applied a qualitative thematic analysis to the collected data. Results: Four informal communication strategies (structured informality, casual tech, implicit communication, and face-to-face opportunity seeking) that were improvised amid the sudden shift to teleworking caused by COVID-19 were identified. Discussion: The findings can inform concrete means for the effective and dynamic transition of informal communication to teleworking settings during emergencies, thus contributing to informal communication studies as well as the promotion of resilient business operations and employee well-being in response to future crises.